Game Design, Gender and Personalities in Programming Education - Theodoropoulos, Anastasios; Lepouras, George (Frontiers in Computer Science, 2022)
Background and Context: There are many programming environments that address the learning needs of students in CS education. In this study, the effects of three different programming environments were investigated, in high school settings, by creating games and taking into account gender and personality characteristics. Personality traits are reflected in students’ pat-terns of thoughts, feelings, and behaviors and to this end we studied both cognitive preferences and emotional intelligence (EQ). Three groups were formed: Group A created games with Scratch, Group B used App Inventor and made games for mobile devices, while Group C created interactive stories-games with Alice 3D Objective: Our study was seeking to find possible biases based on: gender, learning perception, usage and students’ personalities between the three experimental conditions. Therefore, we investigated: i) the role of gender in different programming learning environments, specific personality characteristics, that is the ii) cognitive style and the iii) emotional intelligence. Finally, we research longitudinal emotional effects after the gaming work-shops. Method: 163 students aged 14-15 years old participated in the study, in three experimental groups. Research data were collected through pre and post activity questionnaires. Findings: We found gender preferences for the three programming tools and, in some cases, different personalities (cognitive styles and EQ) have different preferences with regards to the programming environments. All three environments had different emotional effects on the students. Implications: The study concludes with guidelines for programming learning environments that respect individual learning preferences and aim to maximize learning effectiveness.